Effects of sources and meteorology on particulate matter in the Western Mediterranean Basin: An overview of the DAURE campaign. Issue 8 (29th April 2014) - Pandolfi, M.; Querol, X.; Alastuey, A.; Jimenez, J. L.; Jorba, O.; Day, D.; Ortega, A.; Cubison, M. J.; Comerón, A.; Sicard, M.; Mohr, C.; Prévôt, A. S. H.; et al.
Abstract DAURE (Determination of the Sources of Atmospheric Aerosols in Urban and Rural Environments in the Western Mediterranean) was a multidisciplinary international field campaign aimed at investigating the sources and meteorological controls of particulate matter in the Western Mediterranean Basin (WMB). Measurements were simultaneously performed at an urban‐coastal (Barcelona, BCN) and a rural‐elevated (Montseny, MSY) site pair in NE Spain during winter and summer. State‐of‐the‐art methods such as 14C analysis, proton‐transfer reaction mass spectrometry, and high‐resolution aerosol mass spectrometry were applied for the first time in the WMB as part of DAURE. WMB regional pollution episodes were associated with high concentrations of inorganic and organic species formed during the transport to inland areas and built up at regional scales. Winter pollutants accumulation depended on the degree of regional stagnation of an air mass under anticyclonic conditions and the planetary boundary layer height. In summer, regional recirculation and biogenic secondary organic aerosols (SOA) formation mainly determined the regional pollutant concentrations. The contribution from fossil sources to organic carbon (OC) and elemental carbon (EC) and hydrocarbon‐like organic aerosol concentrations were higher at BCN compared with MSY due to traffic emissions. The relative contribution of nonfossil OC was higher at MSY especially in summer due to biogenic emissions. The fossil OC/EC ratio at MSY was twice the corresponding ratio at BCN indicating that a substantial fraction of fossil OC was due to fossil SOA. In winter, BCN cooking emissions were identified as an important source of modern carbon in primary organic aerosol.